Environmental Design in Education and Training: What Do We Know and Where are We Going?. (September 2016) - Stone, Nancy J.; Bazley, Conne Mara; Jacobs, Karen; Robertson, Michelle M.; Boring, Ronald Laurids; Rice, Valerie; Caldwell, Barrett S.
Increasingly, individuals are using more blended, hybrid, and online deliver formats in education and training. Although research exists about how the physical and social environment impact learning and training in traditional face-to-face settings, we have limited knowledge about how the environment affects learners when they are interacting with technology in their learning situations. In particular, concerns arise about levels of engagement, whether learning is enhanced, the impact or helpfulness of robotics, and how the social dynamics change. These five panelists bring expertise in education at the undergraduate and graduate levels, training within industry and the military, and the use of various teaching and training methods. The panelists will present their perspectives to several questions relative to how the environment can (or cannot) accommodate enhanced learning in education and training when technology is involved. Ample time will remain for audience participation.